Designing Management Methods in Elementary School by Creating Enthusiasm to Promote Learning in Students - Samaneh Hoseinpoorian Chabok (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This research seeks to reach common patterns that cause students happiness by introducing schools' open and closed spaces components with Iran and a broad range of traditional and modern school samples, analyzing and expressing them as design criteria. Methodology: Current research addresses studies in psychology, happiness, and students' physical and psychological needs, in addition to a literature review and a necessity for a refreshing school environment by library and field study and content analysis methods.Findings: The inefficiency of educational spaces and inappropriate management functions in happiness and cheerfulness creation among the students to better learning caused this research to design educational space by utilizing principal management approaches and compatible design elements in schools.Originality/Value: Educational environments are the most crucial supplier spaces for society's qualitative power and play an essential role in the interaction of humans from mental and psychological perspectives. Therefore, the slightest attempt that can be made to supply kids with physical and spirited hygiene is to create some joyful spaces in the schools. We can acknowledge every student's comprehensive growth and evolution to ensure that his education duration is provided in physical, cognitive, emotional, ethical, and moral dimensions by cheerfulness and happiness at school. If one of these points gets damaged or forgotten, the student does not achieve the perfect ability and competence.